Design of Virtual Reality for Gonggong Building as a Tourism Information - Safitri , Nur Ramadhani; Andhi, Rahmat Rizal (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2023)
The rapid development of information media in line with the presence of technology increasingly provides convenience for humans so that information or messages can be conveyed properly, quickly, precisely, and usefully. One of the technological developments that support information media is Virtual Reality (VR). Information Media related to Tanjungpinang City Tourism with the object of research in the form of the Gonggong Building as the Tanjungpinang City Tourism Information Center, which has the problem of stopping the function of the Building as a City Tourism Information Center due to damage. The purpose of this research is to implement Virtual Reality on the Gonggong Building with the output of the VR website of the Gonggong Building and the presentation of Tanjungpinang City tourism information content delivered by the Chatbot Tour Guide. The SDLC method used in this research is Prototype. The research results are a VR website for the Gonggong Building, which contains information related to Tanjungpinang City Tourism, namely Typical Culinary Destinations, Nature Tourism, and Melayu Traditional Clothing of the Riau Islands. The result of testing methods with 25010 obtained excellent results with Grade B on performance GTmetrix in testing the efficiency of the system in getting a response time of 5,8s fully loaded time page. From the reliability test results, a summary is obtained in the form of successful session 25964, failed session 0, successful page 25966, failed pages 0, successful hits 51932, failed hits 0, and other errors 0. These results, if expressed in percentage form, amount to 100%.